Survival and Migration of Pre-induced Adult Human Peripheral Blood Mononuclear Cells in Retinal Degeneration Slow (rds) Mice Three Months After Subretinal Transplantation - Peng, Yuting (Bentham Science Publishers, 2014)
Introduction: Retinitis pigmentosa (RP), an inherited disease characterized by progressive loss of photoreceptors and retinal pigment epithelium, is a leading genetic cause of blindness. Cell transplantation to replace lost photoreceptors is a potential therapeutic strategy, but technical limitations have prevented clinical application. Adult human peripheral blood mononuclear cells (hPBMCs) may be an ideal cell source for such therapies. This study examined the survival and migration of pre-induced hPBMCs three months after subretinal transplantation in the retinal degeneration slow (rds) mouse model of RP. Materials and Methods: Freshly isolated adult hPBMCs were pre-induced by co-culture with neonatal Sprague-Dawley (SD) rat retinal tissue for 4 days in neural stem cell medium. Pre-induced cells were labeled with CM-DiI for tracing and injected into the right subretinal space of rds mice by the trans-scleral approach. After two and three months, right eyes were harvested and transplanted cell survival and migration examined in frozen sections and whole mountretinas. Immunofluorescence in whole-mount retinas was used to detect the expression of human neuronal and photorece ptorsprotein markers by transplanted cells. Results: Pre-induced adult hPBMCs could survive in vivo and migrate to various parts of the retina. After two and three months, transplanted cells were observed in the ciliary body, retinal outer nuclear layer, inner nuclear layer, ganglion cell layer, optic papilla, and within the optic nerve. The neuronal and photoreceptor markers CD90/Thy1, MAP-2, nestin, and rhodopsin were expressed by subpopulations of CM-DiI-positive cells three months after subretinal transplantation. Conclusion: Pre-induced adult hPBMCs survived for at least three months after subretinal transplantation, migrated throughout the retina, and expressed human protein markers. These results suggest that hPBMCs could be used for cell replacement therapy to treat retinal degenerative diseases.